Strategies Influencing Achievement in Mathematics and Competence in Soft Skills among Students in Technical Colleges in Kenya - Mutahi, Muthoni David; Gunga, Okuro Samson; John, Mwaruvie; Wairimu, Mutahi Irene (KABARAK UNIVERSITY, 2012)
Mathematics is useful in daily life. It plays an important role in developing students’ logical, creative and critical reasoning, optimize industrial processes, solve problems, function with linear and non-linear thought processes and communicate solutions briefly and precisely among other soft skills. Despite the critical role played by mathematics, low students’ achievement in mathematics and low competence in soft skills had been witnessed. Low achievement and competence in soft skills had been a source of concern to stakeholders in technical and vocational education. That was because the input was not commensurate with the graduate output. Teaching styles in mathematics could be significant in determining the achievement in mathematics and competence in soft skills. Activity-based instructional processes and learning rather than expository means could improve achievement in mathematics and competence in soft skills. Yet, the use of multi-disciplinary approach that depends on using students’ experiences in mathematics and science, project-based teaching and industrial-based activities had not been fully exploited in Kenya at least in East and Central Africa. The purpose of the study was to establish what activities in multi-disciplinary approaches could stimulate interest and deepen understanding of concepts in mathematics in technical colleges in Kenya. The findings and recommendations are expected to inform policy decision in establishing quality and relevance in training and accreditation in mathematics in technical colleges in Africa and world over. The study was carried out by a descriptive survey design. Colleges were enlisted using stratified random sampling. Random numbers were used for picking the sample respondents. Lecturer’s questionnaire was administered to collect data on teaching styles. The results showed that multi-disciplinary approach with problem-solving in projects involving team-work with industrial staff and small group discussions of case studies in class deepened understanding of mathematics concepts served as the basis for industrial competence in soft skills and on-the job training for employability. The strategy of multidisciplinary approach for improving students’ acheievement in mathematics and competence in soft skills in technical colleges in Africa and world over is recommended.
Keywords: Strategies; Students; Students’ collaboration; industrial staff; achievement in Mathematics; Competence and soft skills